Vascular remodeling in arteriovenous fistula treated with PDE5A inhibitors - Maheshika Somarathna; Hannah Northrup; Kevin Ingle; Tatyana Isayeva‐Waldrop; Nguyen Thuy Nhu Nguyen; Bailey Lose; Yan‐Ting Shiu; Timmy Lee (Physiological Reports)
Abstract The arteriovenous fistula (AVF) is the lifeline for hemodialysis patients. However, there are currently no effective therapies promoting AVF maturation. AVF dilation by smooth muscle cell relaxation, through increased cyclic guanosine monophosphate (cGMP), is one potential mechanism to improve AVF remodeling. In this study, we examined the cGMP pathway and its inhibitor phosphodiesterase 5A (PDE5A) in rat, pig, and human AVF. We administered the PDE5A inhibitor, sildenafil, to rats with femoral AVFs and analyzed AVF histological and hemodynamic parameters. We observed that AVF creation increases PDE5A expression in rodent and porcine AVF models. Similarly, we observed an increase in PDE5A expression in the anastomotic regions of AVFs from hemodialysis patients when compared to pre‐AVF placement. Sildenafil‐treated rats showed significantly increased ultrasound‐derived AVF volumetric blood flow and increased MRI‐derived 3‐dimensional lumen diameter when compared to controls. MRI‐based computational fluid dynamics showed that sildenafil‐treated rats had increased anastomotic hemodynamics compared to control rats. Histology showed similar intimal hyperplasia in sildenafil‐treated and control rats. In conclusion, sildenafil treatment increases AVF vein outward expansion and blood flow without affecting the level of intimal hyperplasia. PDE5A inhibitors serve as a potential therapeutic approach to promote AVF maturation by enhancing outward vascular remodeling.